DIPLOMASI EKONOMI JEPANG DALAM UPAYA PERPINDAHAN LIMBAH B3 MELALUI INDONESIA-JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) - Nurshinta Anggia Anggraeni (Universitas Potensi Utama, 2020)
The development of Japan's industrial sector triggered the generation of toxic and hazardous waste as its consequences which endangered the environment and human’s health. The high cost of waste management and limited land disposal encourages transboundary movement to developing countries. Although it has been monitored by the Basel Convention which ban toxic waste movement, Japan still find the loophole by using Indonesia-Japan Economic Partnership Agreement (IJEPA) as an instrument to transfer domestic waste abroad. This study will use the theory of economic diplomacy and issue linkage concept to observe Japan's diplomacy in reaching an agreement on reducing toxic and hazardous waste tariff with Indonesia in IJEPA. The result shows that Japan bartered the issue by offering capacity building compensation. Those are consisting of investment on toxic and hazardous waste management facilities and the development of hazardous waste recycling market in Indonesia. Through the compensation, reduction tariff of hazardous waste could be achieved by Japan to continue its transboundary movement and reduce the impact of domestic environmental pollution, while still accommodating the interests of Indonesia in terms of capacity building towards hazardous waste management.